THE RIGHT TO SELF-DETERMINATION OF NATIVE AND INDIGENOUS PEOPLES. THE CASE OF THE CREE NATION - Coon-Come, Matthew (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1992)
The cultural situation of native American peoples, with specific reference to the Cree people of James Bay.